CuAAC mediated synthesis of cyclen cored glycodendrimers of high sugar tethers at low generation. (October 2021) - Agrahari, Anand K.; Jaiswal, Manoj K.; Yadav, Mangal S.; Tiwari, Vinod K.
Abstract: Glycodendrimers are receiving considerable attention to mimic a number of imperative features of cell surface glycoconjugate and acquired excellent relevance to a wide domain of investigations including medicine, pharmaceutics, catalysis, nanotechnology, carbohydrate-protein interaction, and moreover in drug delivery systems. Toward this end, an expeditious, modular, and regioselective triazole-forming CuAAC click approach along with double stage convergent synthetic method was chosen to develop a variety of novel chlorine-containing cyclen cored glycodendrimers of high sugar tethers at low generation of promising therapeutic potential. We developed a novel chlorine-containing hypercore unit with 12 alkynyl functionality originated from cyclen scaffold which was confirmed by its single crystal X-ray data analysis. Further, the modular CuAAC technique was utilized to produce a variety of novel 12–sugar coated (G0 ) glycodendrimers 12-15 adorn with β -Glc-, β -Man-, β -Gal-, β -Lac, along with 36-galactose coated (G1 ) glycodendrimer 18 in good-to-high yield. The structures of the developed glycodendrimer architectures have been well elucidated by extensive spectral analysis including NMR ( 1 H & 13 CNMR), HRMS, MALDI-TOF MS, UV–Vis, IR, and SEC (Size Exclusion Chromatogram) data. Graphical abstract: Image 1 Highlights: A series of Cyclen Cored Glycodendrimer has been achieved with high Sugar Tethers at Low Generation by using modular CuAAC 'Click Chemistry'. A double stage convergent protocol was explored to facilitate generation of 36-galactose coated (G1 ) glycodendrimer. The developed sugar coated (G0 ) glycodendrimers have been characterized by its NMR, MALDI-TOF, UV–Vis, IR, and SEC analysis. The high functional group density at the low generation of glycodendrimer may open a new area for the carbohydrate-protein interaction.